The ZVS-PWM commutation cell applied to the DC-AC converter - Mendes de Seixas, Falcondes José [UNESP]; Martins, Denizar Cruz (Institute of Electrical and Electronics Engineers (IEEE), 1997)
This paper presents the analysis of a dc-ac converter using a zero-voltage-switching (ZVS) commutation cell. First, we show the cell applied to the buck converter. The stages of operation are presented along with the main current and voltage equations. Next, we adapt the converter to the regenerative-operation mode. Hence, the full-bridge converter at low-frequency operation is connected in the dc-dc output stage (at high frequency). The main switches commute at zero voltage. The converter operated at constant frequency with pulse-width modulation (PWM), and neither overvoltage nor additional current stress was observed by digital simulation. A design example and experimental results obtained by prototype, rated at 275 V and 1 kW, are also presented. © 1997 IEEE.
Keywords: DC-AC converter; Power electronics; Pulse-width modulation; Soft switching; Electric network analysis; Electric network topology; Performance; Pulse width modulation; Switching circuits; Zero voltage switching commutation cell; Electric inverters